Pelatihan Pembuatan Buket Makanan Ringan Pada PKK Grand Citayam Training on Snack Bouquet Making for PKK Grand Citayam - Desnaranti, Laila; Putra , Febby Pratama; Anggini, Wulan Yulian (KANGMAS: Karya Ilmiah Pengabdian Masyarakat, 2025)
The Covid-19 pandemic has caused many people to lose their source of income. This has caused housewives who previously had a role in taking care of the household to step in in finding solutions to increase income or even create new income sources. Entrepreneurship is expected to help people affected by Covid-19. Entrepreneurship is one of the activities that can assist housewives gain or grow income for their families. To overcome this, training is needed to make a product that can that can be manufactured at a low cost. This training can foster interest in entrepreneurship as well as creativity and innovation from housewives. It is also hoped that with entrepreneurial activities, in addition to increasing income, it can also help the economy so that allowing housewives to meet their basic necessities. The output obtained from this community service activity is a product in the form of a snacks bouquet with minimal capital